2018
DOI: 10.3390/molecules23123270
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study on the Synergistic Inhibition Effect of Pyridine Derivatives and Sulfur-Containing Compounds on the Corrosion of Carbon Steel in CO2-Saturated 3.5 wt.% NaCl Solution

Abstract: The corrosion inhibition performance of pyridine derivatives (4-methylpyridine and its quaternary ammonium salts) and sulfur-containing compounds (thiourea and mercaptoethanol) with different molar ratios on carbon steel in CO2-saturated 3.5 wt.% NaCl solution was investigated by weight loss, potentiodynamic polarization, electrochemical impedance spectroscopy, and scanning electron microscopy. The synergistic corrosion inhibition mechanism of mixed inhibitors was elucidated by the theoretical calculation and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 55 publications
(60 reference statements)
1
17
0
Order By: Relevance
“…As seen from the Nyquist plots, a single depressed capacitive semicircle is presented in all the Nyquist plots, and the capacitive semicircle radius increases obviously after adding inhibitors in the test solution. This result reveals that the addition of hybrid inhibitor did not change the mechanism of the corrosion process, but inhibited corrosion by forming a protective film on the steel surface [ 40 , 41 ], which is consistent with the results of polarization curves. For each kind of hybrid inhibitor, as the inorganic inhibitor ratio increases, the capacitive semicircle radius of Nyquist plots decreases obviously.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As seen from the Nyquist plots, a single depressed capacitive semicircle is presented in all the Nyquist plots, and the capacitive semicircle radius increases obviously after adding inhibitors in the test solution. This result reveals that the addition of hybrid inhibitor did not change the mechanism of the corrosion process, but inhibited corrosion by forming a protective film on the steel surface [ 40 , 41 ], which is consistent with the results of polarization curves. For each kind of hybrid inhibitor, as the inorganic inhibitor ratio increases, the capacitive semicircle radius of Nyquist plots decreases obviously.…”
Section: Resultssupporting
confidence: 84%
“…In the equivalent circuit, R s stands for the solution resistance and R ct represents the charge-transfer resistance corresponding to the corrosion reaction at the metal substrate/solution interface. C dl is replaced by constant phase elements (CPEs), which are used in the model to compensate for the non-homogeneous electrode surface [ 15 , 41 , 42 ]. R film and C film represent the resistance and capacitance, respectively, of the protective film formed on Q235 steel surface, which includes passivation film, precipitation film, and adsorption film.…”
Section: Resultsmentioning
confidence: 99%
“…The potentiodynamic measurements presented in Figure 5 showed that the cathodic current density of the system was greatly reduced after the addition of GA in the solution, suggesting that GA was able to suppress the hydrogen evolution reaction (Equation (11)) to some extent. Similar results were also confirmed by other authors [21,[26][27][28].…”
Section: Adsorption Via Hydrogen Bond Formation Interactionmentioning
confidence: 99%
“…The literature reports that over the last decades the use of corrosion inhibitors as a means to mitigate CO 2 corrosion that occurs inside the carbon steel pipelines has received a wide interest. Nitrogen-based compounds such as pyridine derivatives [ 11 ] imidazolines [ 12 ], benzimidazole derivatives [ 13 ], and amines [ 14 ] were found to be effective corrosion inhibitors against CO 2 corrosion. However, most of these compounds are reported to be toxic and their synthesis can be very expensive [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result is indicative of the adsorption of additives on the steel surface. With respect to mild steel immersion in 3.5% NaCl solution, reduction of oxygen and dissolution of iron constitute cathodic and anodic electrochemical reactions, respectively [39]. Special inspection of Figure 6a indicates that the inhibition of the anodic branch in the presence of 25 mg/L SCDP/CA assembly is more significant than that in the presence of 125 mg/L SCDP suggesting an enhanced inhibition effect of anodic dissolution by the molecular assembly.…”
Section: Resultsmentioning
confidence: 99%